2010
DOI: 10.1016/j.cognition.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Biological motion cues trigger reflexive attentional orienting

Abstract: The human visual system is extremely sensitive to biological signals around us. In the current study, we demonstrate that biological motion walking direction can induce robust reflexive attentional orienting. Following a brief presentation of a central point-light walker walking towards either the left or right direction, observers' performance was significantly better on a target in the walking direction compared with that in the opposite direction even when participants were explicitly told that walking dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 56 publications
10
94
0
Order By: Relevance
“…Using point-light displays of moving walkers, it has been shown that both human and nonhuman (e.g., a cat) biological motion can cue attention in a congruent direction, even when this is a counterpredictive cue to subsequent targets. Moreover, this effect disappears both with inverted motion orientation and nonbiological motion stimuli (Shi, Weng, He, & Jiang, 2010). These results indicate that reflexive attention may be specialized for biological motion direction.…”
Section: Covert Attention To Action Action In Covert Cueing Paradigmsmentioning
confidence: 56%
“…Using point-light displays of moving walkers, it has been shown that both human and nonhuman (e.g., a cat) biological motion can cue attention in a congruent direction, even when this is a counterpredictive cue to subsequent targets. Moreover, this effect disappears both with inverted motion orientation and nonbiological motion stimuli (Shi, Weng, He, & Jiang, 2010). These results indicate that reflexive attention may be specialized for biological motion direction.…”
Section: Covert Attention To Action Action In Covert Cueing Paradigmsmentioning
confidence: 56%
“…Different from inanimate object motions, humans have evolved to be highly sensitive to other biological entities' movements, quickly understanding the intentions behind their movements and anticipating their next move (12)(13)(14), even when the motions are portrayed by only a handful of point lights attached to the head and major joints (15). The evolutionary importance of biological motion processing makes it special and distinguishes it from other forms of motion (16).…”
mentioning
confidence: 99%
“…Indeed, it has been demonstrated that the walking direction of point-light walkers can be incidentally processed [37] and even induce reflexive attentional orienting [21], suggesting an intrinsic sensitivity of the human visual attention system to biological motion signals [17,38,39]. Because a fast moving biological entity is more likely to signal a threat, it is thus crucial for an organisms survival to quickly and precisely judge its moving direction in order to make an appropriate response (e.g., fight-or-flight reaction).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the human visual system has specialized mechanisms tuned to different face viewpoints [18,19] and body orientations [20]. Although motion can provide more reliable and compelling direction information than a static frame [21], the role of the motion signals is still unclear, as well as whether local motion itself can influence viewpoint discrimination in biological motion. While many previous studies have focused on the global aspects of biological motion perception and have emphasized the contribution of the global configuration [13,22,23], some recent findings also provide evidence highlighting the unique role of local motion signals (e.g., the motion of the feet) in biological motion processing.…”
mentioning
confidence: 99%